2022
DOI: 10.3389/fnmol.2022.912146
|View full text |Cite
|
Sign up to set email alerts
|

Under or Absent Reporting of Light Stimuli in Testing of Anxiety-Like Behaviors in Rodents: The Need for Standardization

Abstract: Behavioral neuroscience tests such as the Light/Dark Test, the Open Field Test, the Elevated Plus Maze Test, and the Three Chamber Social Interaction Test have become both essential and widely used behavioral tests for transgenic and pre-clinical models for drug screening and testing. However, as fast as the field has evolved and the contemporaneous involvement of technology, little assessment of the literature has been done to ensure that these behavioral neuroscience tests that are crucial to pre-clinical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 413 publications
0
8
0
Order By: Relevance
“…It is important to note that when testing different strains of mice, it would be essential to validate the testing or scoring procedure ( Valentinuzzi et al, 1998 ). To avoid artificially inflated lighting sources and thus ensure freezing behavior is induced in a well-controlled manner, it is suggested to report Lux and control the lighting properly ( Neuwirth et al, 2022 ). When a neutral cue or context [a sound, light, or conditioned stimulus (CS)] occurs with a highly aversive signal or unconditioned stimuli (US) and leads to fear behaviors or conditioned fear responses (CRs), which include freezing, a systemic response to behavior besides breathing, fear acquisition arises [47].…”
Section: Gabaergic System and Ptsdmentioning
confidence: 99%
“…It is important to note that when testing different strains of mice, it would be essential to validate the testing or scoring procedure ( Valentinuzzi et al, 1998 ). To avoid artificially inflated lighting sources and thus ensure freezing behavior is induced in a well-controlled manner, it is suggested to report Lux and control the lighting properly ( Neuwirth et al, 2022 ). When a neutral cue or context [a sound, light, or conditioned stimulus (CS)] occurs with a highly aversive signal or unconditioned stimuli (US) and leads to fear behaviors or conditioned fear responses (CRs), which include freezing, a systemic response to behavior besides breathing, fear acquisition arises [47].…”
Section: Gabaergic System and Ptsdmentioning
confidence: 99%
“…In all behavioral tests, a white LED light with diffuser plate was suspended 2.5 meters above the center of the apparatus, and the illumination of the apparatus floor was approximately 50 Lux. Previous study reported this illumination may have neither anxiogenic stimulus nor anxiolytic stimulus ( Neuwirth et al, 2022 ).…”
Section: Methodsmentioning
confidence: 85%
“…It is important to emphasize that other factors were controlled during the experimental battery, such as lighting that can provoke behavioral alterations 81 . The light intensity was adjusted in different protocols to minimize light as an aversive factor and avoid compromising performance, which could lead to anxiogenic behaviors described in the literature 82 , based on previously published protocols.…”
Section: Discussionmentioning
confidence: 99%